Detection of rarely identified multiple mutations in MECP2 gene do not contribute to enhanced severity in rett syndrome. Issue 7 (21st May 2013) - Chapleau, Christopher A.; Lane, Jane; Kirwin, Susan M.; Schanen, Carolyn; Vinette, Kathy M.B.; Stubbolo, Danielle; MacLeod, Patrick; Percy, Alan K.
Abstract The objective of our study was to characterize the influence of multiple mutations in the MECP2 gene in a cohort of individuals with Rett syndrome. Further analysis demonstrated that nearly all resulted from de novo in cis mutations, where the disease severity was indistinguishable from single mutations. Our methods involved enrolling participants in the RTT Natural History Study (NHS). After providing informed consent through their parents or principal caretakers, additional molecular assessments were performed in the participants and their parents to assess the presence and location of more than one mutation in each. Clinical severity was assessed at each visit in those participants in the NHS. Non‐contiguous MECP2 gene variations were detected in 12 participants and contiguous mutations involving a deletion and insertion in three participants. Thirteen of 15 participants had mutations that were in cis; four (of 13) had three MECP2 mutations; two (of 15) had mutations that were both in cis and in trans (i.e., on different alleles). Clinical severity did not appear different from NHS participants with a single similar mutation. Mutations in cis were identified in most participants; two individuals had mutations both in cis and in trans. The presence of multiple mutations was not associated with greater severity. Nevertheless, multiple mutations will require greater thought in the future, if genetic assignment to drug treatment protocols is considered. © 2013 Wiley Periodicals, Inc.